2021
DOI: 10.3390/ijms22189783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aberrations of DNA Repair Pathways in Prostate Cancer: Translation to the Clinic

Abstract: Prostate cancer (PC) is the second most common cancer in men worldwide. Due to the large-scale sequencing efforts, there is currently a better understanding of the genomic landscape of PC. The identification of defects in DNA repair genes has led to clinical studies that provide a strong rationale for developing poly (ADP-ribose) polymerase (PARP) inhibitors and DNA-damaging agents in this molecularly defined subset of patients. The identification of molecularly defined subgroups of patients has also other cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…When the genetic test result has consequences for the treatment of cancer, it is important that turnaround times for genetic testing are minimized. For patients with ovarian cancer and prostate cancer for example, there is clear evidence that patients carrying a pathogenic variant in a BRCA gene have the highest response rates to PARP inhibitors [ 5 , 46 ]. The longest delay in the turnaround time for the standard genetic testing pathway is probably the time between referral and first appointment with a genetic counselor due to long waiting lists [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the genetic test result has consequences for the treatment of cancer, it is important that turnaround times for genetic testing are minimized. For patients with ovarian cancer and prostate cancer for example, there is clear evidence that patients carrying a pathogenic variant in a BRCA gene have the highest response rates to PARP inhibitors [ 5 , 46 ]. The longest delay in the turnaround time for the standard genetic testing pathway is probably the time between referral and first appointment with a genetic counselor due to long waiting lists [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germline BRCA mutations are also common in some particular scenarios of other malignancies, such as triple-negative breast cancer and metastatic castration resistance prostate cancer. In the latter one, germline BRCA mutations occur in 11-33% of the cases, which is considerably higher than the occurrence in localized disease ( 2 ).…”
Section: Introductionmentioning
confidence: 87%
“…It has been shown that combination therapy is associated with significantly higher rates of metastasis-free survival, compared with ADT alone [17]. Moreover, one of the new therapeutic perspectives is the use of the PPAR inhibitor, olaparib, which acts synergistically with the HSP90 inhibitor (AT13387), which has so far been confirmed in clinical trials in mCRPC patients [18]. The greatest problem in the treatment of prostate cancer is the resistance of these cells to treatment aimed at inducing apoptosis, controlling signaling pathways responsible for cell proliferation or modulating the activity of the androgen receptor.…”
Section: Introductionmentioning
confidence: 99%